Estimating Typhoon Haiyan’s Wind Speeds Using Windicators - Agar, Joshua; Mata, William; Hernandez, Jaime Jr. (Philippine Engineering Journal; Vol 39 No 1 (2018), 2018)
Abstract – Typhoon Haiyan of 2013, by the time it struck the Philippines, has been regarded as one of the strongest tropical cyclones. Yet there are discrepancies between the estimated maximum wind speeds reported by the weather agencies worldwide, causing widespread confusion. In the absence of credible in-situ wind speed measurements that will provide the storm’s true strength, “Windicators” are analyzed. Windicator, coined from the terms wind and indicator, are existing simple structures of interest through failure analysis would directly provide an estimate of the wind speeds that brought the bending or even toppling of the structure. The study includes an expansive field survey on affected areas, excluding inundated areas, in Region VIII, where the storm made landfall at peak intensity. Computational Fluid Dynamics (CFD) was used to determine the wind speeds that initiated the failure, either yielding or localized buckling.  The direction of failure/deformation is taken into account in order to establish an estimated time of failure, which in turn directly reflects on the proximity of the storm at the time of the arrival of the winds that caused the structural failure. Using digital image correlation of the satellite images or the gradient wind equation from the approximation of pressure profile of the storm, the radial profile of the storm, before and during landfall are established.This can then be used to estimate the winds on the cyclone’s eyewall from the computed wind speed experienced by the windicator. The study determined through analysis of five windicators, that Typhoon Haiyan has 1-minute sustained winds of 351 kph, 10-minute sustained winds of 290 kph, both estimated intensities before landfall at Leyte, and a minimum central pressure of 872.2 mbar, using Holland’s approximation and from the recorded pressure of 910 mbar from Guiuan Weather Station of PAGASA.   Keywords—Windicators; Typhoon Haiyan; Forensic Structural Analysis; Computational Fluid Dynamics; Wind Engineering; Geophysical Fluid Dynamics